Quality Management for Holistic School Well-Being: The Case of an Indonesian Muhammadiyah Vocational School - Isti Wulandari; Hendro Widodo; Sukirman Sukirman (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah kendari, 2026)
Quality management in education plays a crucial role in enhancing school quality and promoting the well-being of all stakeholders. School well-being is reflected through four key indicators: having, being, loving, and health. When quality management is implemented effectively, it fosters a conducive learning environment that supports the holistic well-being of the entire school community. This study aims to explore how quality management is implemented to realize school well-being at SMK Muhammadiyah 1 Bambanglipuro. Employing a qualitative case study approach, data were collected through interviews, observations, and document analysis. The findings indicate that the school’s quality management practices are manifested in five major themes: (1) a comfortable and enjoyable learning environment; (2) strong family-like relationships; (3) participatory and pleasant school governance; (4) achievement of graduate competencies; and (5) a system of appreciation and rewards. The study concludes that effective quality management contributes positively to overall school well-being. Notably, SMK Muhammadiyah 1 Bambanglipuro implements a Teaching Factory model supported by an industry-based curriculum (Astra and Daihatsu), accompanied by teacher and staff rewards such as Umrah programs, which collectively enhance school well-being.